2006
DOI: 10.1073/pnas.0605284103
|View full text |Cite
|
Sign up to set email alerts
|

Lateral positioning at the dorsal midline: Slit and Roundabout receptors guide Drosophila heart cell migration

Abstract: Heart morphogenesis requires the coordinated regulation of cell movements and cell-cell interactions between distinct populations of cardiac precursor cells. Little is known about the mechanisms that organize cardiac cells into this complex structure. In this study, we analyzed the role of Slit, an extracellular matrix protein and its transmembrane receptors Roundabout (Robo) and Roundabout2 (Robo2) during morphogenesis of the Drosophila heart tube, a process analogous to early heart formation in vertebrates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 27 publications
3
70
0
Order By: Relevance
“…Thus, one possibility is that COMs are attracted to the heart tip via Slit-Robo signaling and that inability of COMs to interact with the heart tip in a slit mutant background contributes to the slowdown in HANC cell movements. The potential role of Slit in COM attraction is in agreement with expression of Slit in the cardioblasts (26)(27)(28) and Robo2 in COM muscles and is supported by the disrupted COM-heart cell contact in a musclespecific knockdown of robo2 via RNAi (Fig. 4J).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Thus, one possibility is that COMs are attracted to the heart tip via Slit-Robo signaling and that inability of COMs to interact with the heart tip in a slit mutant background contributes to the slowdown in HANC cell movements. The potential role of Slit in COM attraction is in agreement with expression of Slit in the cardioblasts (26)(27)(28) and Robo2 in COM muscles and is supported by the disrupted COM-heart cell contact in a musclespecific knockdown of robo2 via RNAi (Fig. 4J).…”
Section: Resultssupporting
confidence: 62%
“…We first attempted to determine whether the candidate molecules are expressed in migrating HANC cells and the anterior heart tube. It has been shown that Slit is expressed in cardioblasts and in pericardial cells during embryonic stages 14 and 15 along the entire cardiac primordium (26)(27)(28). Slit expression was also observed in the head region in cells that form the invaginating dorsal pouch (38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, Slit/ Robo signaling also prevents tracheal, sensory precursor cells, and cardiac cells from approaching the midline (Lundstrom et al, 2004;Orgogozo et al, 2004;Santiago-Martinez et al, 2006). In vertebrates, a similar function for Slit/Robo in the control of neuronal migration at the midline has not been demonstrated.…”
Section: Discussionmentioning
confidence: 98%